Study of pesticide poisoning in an Agricultural Community in Sri Lanka - Abeysinghe, M.R.N (My University, 1992)
The objectives of this study were to determine the incidence rates of pesticide poisoning in an agricultural community and identification of the factors influencing them. An incidence rate of 301.9 per 100,000 population was estimated for the general population. A knowledge score was developed for both the users and the non-users of pesticides and a practice score was developed for the users. The finding indicate that immediate remedial measures are needed for the control of the high incidence of suicides, using pesticides as the means. Practicable intervention programmes should be introduced to prevent the occupational pesticide poisonings, as it was found that practices of pesticide users were not satisfactory unlike their level of knowledge.